Generation X versus Generation Y household heads an analysis of household and expenditure differences - Del Mundo, Daphne Anne A.; Sumait, Rojean Janis A.; Reside, Renato Jr. E. (Quezon City School of Economics, University of the Philippines Diliman, 2018)
Objectives. This paper aims to analyze the differences between households headed by people born in Generation X and Generation Y. It intends to determine the household head characteristics in each cohort and examine how these affect the household expenditures and characteristics. Methods. Using data from the Family Income and Expenditure Survey (FIES), households are grouped based on the generational cohort of the household. Households headed by people born in Generation X are drawn and pooled from the 1985, 1988, 1991, and 1994 FIES data. On the other hand, households with Generation Y_born heads are drawn and pooled from the 2006, 2009, 2012, and 2015 FIES data. Multiple linear regression and logistic regression are used to determine the factors that affect certain expenditures and characteristics of households. Results. Results show that total expenditure of a household head is highest for both generations when educational attainment is high and in an urban settlement, for Gen X when single (no difference for sex), and for Gen Y when widowed and female. Total savings of a household head is highest for both generations when single, educational attainment is low and in a rural settlement, and for Gen Y when male (no difference for sex for Gen X). Total medical expenditure of a household head is highest for both generations when educational attainment is high (no difference for urbanity and sex), for Gen X when married, and for Gen Y when divorced. The probability of living in an apartment rather than a single house is highest for both generations when educational attainment is high, in a rural settlement, and there are more household members, for Gen X when single or separated, female, and young. The probability of owning a car is highest for both generations when educational attainment is high and household head is older, for Gen X when male, and income is high, for Gen Y when head is single, in an urban settlement, and there are more household members. The probability of owning a television is highest for both generations when household head is married, has high educational attainment, is female, older, in an urban settlement and have high income. Contribution. Macroeconomic points of views are easy to point out and explain as to why expenditure patterns or trends then to move in the way that it is moving., e.g., economic downturns, health outbreaks, political turmoils, etc. So, this study is aimed to explain expenditure pattern in a microeconomic point of view, i.e., household heads are the ones that are analyzed. In extension, the households were agglomerated to their respective generations_ X and Y, and are compared with each other to show interesting differences between these generations.
Thesis (B.S. Business Economics) -- University of the Philippines Diliman
Keywords: Heads of households -- Economic conditions -- Philippines; Generation X -- Economic conditions -- Philippines; Generation Y -- Economic conditions -- Philippines